Russian immigrants in the United States : adapting to American culture - Kishinevsky, Vera, 1953- (New Americans (LFB Scholarly Publishing LLC), 2004)
Kishinevsky's study surveys the acculturation of and response to American culture by three generations of Russian immigrant women. Kishinevsky tells the stores of three generations of women who immigrated to the United States from Russia and satellite states, inviting the reader into their reality and presenting their worldviews, attitudes and perspectives through powerful and exciting life stories. She interviewed five triads of immigrant women (retired grandmothers, midlife mothers and teenage daughters). Her analysis of these powerful pieces yields unexpected conclusions about the strength of family ties and intergenerational influences that continue to shape the worldview of young Russian-Americans. The book is written from a multicultural perspective exploring such general issues as acculturation, assimilation and psychological adjustment of immigrants as it applies to the Russian immigrants.